1977
DOI: 10.1159/000468311
|View full text |Cite
|
Sign up to set email alerts
|

Transmethylation Hypothesis of Schizophrenia: Methionine and Nicotinic Acid

Abstract: The transmethylation hypothesis of schizophrenia was reviewed with considerations that large doses of methionine when combined with a monoamine oxidase inhibitor lead to exacerbation of psychotic symptoms in a significant percentage of chronic schizophrenic patients. It was noted that nicotinic acid in the dosage of 3,000 mg/day can neither prevent nor counteract the psychopathology thus induced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 68 publications
0
7
0
1
Order By: Relevance
“…There are other modern theories of schizophrenia that can provide an explanation to this contradiction. [57][58][59] The specific mechanisms by which L-theanine exerts its neuroprotective action are just beginning to be studied and clarified. L-Theanine acts antagonistically against the stimulatory effects of caffeine on the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…There are other modern theories of schizophrenia that can provide an explanation to this contradiction. [57][58][59] The specific mechanisms by which L-theanine exerts its neuroprotective action are just beginning to be studied and clarified. L-Theanine acts antagonistically against the stimulatory effects of caffeine on the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Certain other investigators have likewise proposed a hypothesis known as the “transmethylation hypothesis of schizophrenia”, which expresses that the regularly occurring biogenic amines like indolamine methylates into the shape of a methylated amine which leaves a daydreaming effector a hallucinating impact in schizophrenic patients. 29-31…”
Section: Schizophreniamentioning
confidence: 99%
“…Interestingly, it has been reported that the high consumption of methionine could promote brain damage. In the past, the transmethylation theory of schizophrenia was proposed, based on the fact that methyl donors such as methionine can exacerbate psychotic symptoms [ 22 25 ]. Additionally, recent clinical studies link high levels of plasma methionine sulfoxide, an intermediate in the methionine cycle, with ageing and Alzheimer’s disease (AD) [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%